Critical review of integrated water resources management: Moving beyond polarised discourse - V. S. Saravanan; Geoffrey T. McDonald; Peter P. Mollinga (University of Bonn, Center for Development Research (ZEF), 2008)
IWRM has emerged as a popular ideology in the water sector since the 20th century. From a highly techno-centric approach in the past, it has taken a new turn worldwide, following a Habermasian communicative rationality, as a place-based nexus for multiple actors to consensually and communicatively take decisions in a hydrological unit. This communicative practice expects to be consensual, stable and static in integration of water management. This how IWRM should be approach had a remarkable appeal worldwide as promoting authentic participation of all stakeholders in integrating water management. Its Foucauldian critiques argue how IWRM cannot be achieved given the power dynamics in social interactions. The critiques reveal that the domain of water resources management is a discursive terrain of collective action, contestation and negotiation, making water management a socio-political process, where there are multiple forms and meanings of integration. The emphasis is on complexities, contextuality, power dynamics and importance of analysing real world situations, but without proposing any concrete actions. These apparently contradictory discourses depict a polarised world of water management, without offering any insights for future water resource management. On one hand, the Habermasian communicative practice emphasises on 'ideal speech situations', in which no affected party is excluded from discourse or by asymmetries of power for collective decisions. On the other hand, the Foucauldian theory argues for analysing the real world situation of integration and the power dynamics. A prospective option to further the integration of water resource management is to consider these apparently contradictory discourses as interdependent by examining how integration actually does take place in a strategic context, notwithstanding the absence of Habermasian conditions and the presence of Foucauldian relations of power.
urn:nbn:de:0202-20080911298
Keywords: 330; water management; IWRM; policy; power